Fault diagnosis of cracks in crystalline silicon photovoltaic modules through I-V curve. (November 2020) - Ma, Mingyao; Zhang, Zhixiang; Xie, Zhen; Yun, Ping; Zhang, Xing; Li, Fei
Abstract: Photovoltaic (PV) cell cracks in wafer-based silicon PV modules are a well-known problem. In order to extract the fault characteristics of the cracked PV modules, we investigate and collect the cracked PV modules in several large PV power plants. The I-V characteristics of the cracked PV modules are tested. The test results show that the I-V curves of the cracked PV modules show a convex function step, and the reason for the I-V characteristics of the cracked PV module is analysed. A method for online diagnosis of PV module crack through I-V curve is proposed. Highlights: Non-uniformity of crack causes inconsistent characteristics of cells. The step of cracked PV module I-V curve shows a convex function feature. I-V curve is derived to detect the step and the step type is determined by the current difference. Online diagnosis of cracks in photovoltaic modules based on I-V curve.